Glibenclamide Advantage in Treating Edema After Intracerebral Hemorrhage (GATE-ICH): Study Protocol for a Multicenter Randomized, Controlled, Assessor-Blinded Trial - Zhao, Jingjing; Yang, Fang; Song, Changgeng; Li, Li; Yang, Xiai; Wang, Xiaofeng; Yu, Liping; Guo, Jun; Wang, Kangjun; Fu, Feng; Jiang, Wen (Frontiers in Neurology, 2021)
Introduction: Brain edema after acute intracerebral hemorrhage (ICH) plays a critical role in the secondary injury of ICH and may heighten the potential for a poor outcome. This trial aims to explore the efficacy of small doses of oral glibenclamide in perihematomal edema (PHE) and the prognosis of patients with ICH. Methods and Analysis: The GATE-ICH trial is a multicenter randomized, controlled, assessor-blinded trial. A total of 220 adult patients with acute primary ICH in 28 study centers in China will be randomized to the glibenclamide group (glibenclamide plus guideline-recommended ICH management) or the control group (guideline-recommended ICH management). Multivariate logistic regression will be used to analyze the relationship between the treatments and primary outcome. Study Outcomes: The primary efficacy outcome is the proportion of poor functional outcomes (modified Rankin Scale ≥3) at 90 days after enrollment. The secondary efficacy outcomes include changes in the volume of ICH and PHE between the baseline and follow-up computed tomography scans as well as the clinical scores between the baseline and follow-up assessments. Discussion: The GATE-ICH trial will assess the effects of small doses of oral glibenclamide in reducing the PHE after ICH and improving the 90-day prognosis of patients. Clinical Trial Registration:www.clinicaltrials.gov., NCT03741530. Registered on November 8, 2018. Trial Status: Protocol version: May 6, 2019, Version 5. Recruitment and follow-up of patients is currently ongoing. This trial will be end in the second quarter of 2021.